Thrombin-mediated In Vitro Processing of Pro-von Willebrand Factor - Váradi, Katalin; Turecek, Peter L.; Mitterer, Artur; Dorner, Friedrich; Schwarz, Hans Peter (Thrombosis and Haemostasis, 2001)
Von Willebrand factor (vWF) is synthesized in endothelial cells as pre-provWF and processed intracellularly to propeptide (vWFpp) and mature vWF. Building on previous studies indicating that recombinant provWF when infused into animals can also be processed extracellularly in vivo, we investigated the processing of provWF in vitro. Incubation of a recombinant provWF (rpvWF) preparation with canine and human vWF-deficient plasma induced a time-dependent decrease in provWF antigen and an increase in vWFpp antigen without changing total vWF antigen or collagen-binding activity. Multimer analysis showed the gradual transformation of the provWF multimers to mature vWF multimers and cleaved vWFpp was visualized on autoradiograms of SDS-polyacrylamide electrophoresis gels using 125I-labeled provWF. Processing was facilitated by CaCl2, but prevented by a thrombin inhibitor and did not occur in prothrombin-depleted plasma. When recombinant provWF was incubated with increasing amounts of purified thrombin, the extent of provWF processing was dose-dependent. The specific cleavage of vWFpp was confirmed by immunoblots using an anti-vWFpp antibody and by amino terminal amino-acid analysis. Binding of provWF to collagen decreased the thrombin concentration necessary for propeptide removal to a concentration in the range of that found during blood clotting. Meizothrombin, an intermediate of prothrombin activation, was also able to induce dose-dependent removal of the propeptide from rpvWF. Hirudin preconditioning of vWF-deficient mice attenuated processing of infused rpvWF suggesting that thrombin plays a part in the processing events in vivo.
Keywords: Von Willebrand factor (vWF); propeptide; provWF; thrombin; processing